Phosphate adsorption in three soils of the Rio Grande do Norte semiarid region - Godinho, Vicente de Paulo Campos; Sampaio, Regynaldo Arruda; Venegas, Victor Hugo Alvarez; Ruiz, Hugo Alberto (Pesquisa Agropecuaria Brasileira, 1997)
To evaluate phosphate adsorption in Rio Grande do Norte semiarid soils, laboratory determinations were made utilizing samples collected at up to 20 cm of depth, from a Vertisol (V) and two Fluvents (Ae1 and Ae2). In these soils remaining phosphorus was determined after agitation of the samples with a solution of CaCl2 10 mmol/L containing 60 mg/L of P, for one hour. The phosphorus doses for Langmuir isotherm adjustment were defined based on the remaining P values and corresponded to 0.0; 6.0; 12.0; 18.0; 30.0; 42.0; 54.0; 66.0; 84.0; 102.0; and 120.0 mg/L. The data of adsorbed P and the concentrations of equilibrium solutions obtained after 24-hour agitation of soil samples with the solutions of CaCl2 10 mmol/L containing the above-cited P concentrations, were adjusted to Langmuir isotherm. Three different adsorption regions were identified and adjusted to linear regression models. The maximum phosphate adsorption capacity (CMAF) and the constant related to the adsorption energy of phosphates (EAF) were determined. The CMAF presented values of 0.312; 0.291 and 0.249 mg of P/cm3 of soil for soils V, Ae1 and Ae2, respectively. Phosphate adsorption was strongly influenced by the specific surface and P content of the soils. In soils V and Ae1, the remaining phosphorus decreased with and increase in the clay content, while CMAF and EAF increased with an increase in clay.